2004
DOI: 10.1097/01.ta.0000084518.09928.ca
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Fractures and Associated Injuries in Children

Abstract: The majority of pelvic fractures in children may be satisfactorily treated nonoperatively. Operative interventions were more frequently required for associated injuries. Long-term review is indicated because of delayed complications in children that are continuing to grow and develop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
1
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 24 publications
9
73
1
9
Order By: Relevance
“…As fraturas do anel pélvico em pacientes esqueleticamente imaturos são relativamente raras, representam menos de 0,2% de todas as fraturas pediátricas e 1 a 5% das admissões em centros terciários de trauma infantil (1,2) . Geralmente causadas por trauma de alta energia é frequente a associação a outras lesões orgânicas (aparelho geniturinário, vísceras abdominais, sistema nervoso central, estruturas neurovasculares e musculoesqueléticas) (3) .…”
Section: Introductionunclassified
“…As fraturas do anel pélvico em pacientes esqueleticamente imaturos são relativamente raras, representam menos de 0,2% de todas as fraturas pediátricas e 1 a 5% das admissões em centros terciários de trauma infantil (1,2) . Geralmente causadas por trauma de alta energia é frequente a associação a outras lesões orgânicas (aparelho geniturinário, vísceras abdominais, sistema nervoso central, estruturas neurovasculares e musculoesqueléticas) (3) .…”
Section: Introductionunclassified
“…In a published clinical series involving 585 patients with pelvic fractures, 87% were reported as having at least one, and often several, associated injuries [17][18][21][22][23]. Grisoni,et al [19] reported in their series, 58% with involvement of one or more other body areas, including nonpelvic fractures (49%), neurological injury (26%), significant haemorrhage requiring transfusion (21%), abdominal injury (14%), thoracic injury (7%), and genitourinary injury (4%).…”
Section: Associated Injuriesmentioning
confidence: 99%
“…Thus, the presence of a pelvic fracture in a child is a marker of severe injury. Children with pelvic fractures may require blood transfusion; however, death by exsanguination or associated vascular injury is unlikely [17][18][19] as compared to adults because of more effective vasoconstrictive response with nonatherosclerotic blood vessels [20]. In children with unstable fracture patterns or uncontrolled hypotension with ongoing transfusion requirements, external fixation, angiography and selective embolization may be indicated.…”
Section: Physiological Consideration In a Childmentioning
confidence: 99%
See 2 more Smart Citations